2021
DOI: 10.18632/aging.203203
|View full text |Cite
|
Sign up to set email alerts
|

The lack of functional DNMT2/TRDMT1 gene modulates cancer cell responses during drug-induced senescence

Abstract: Cellular senescence may be a side effect of chemotherapy and other anti-cancer treatments that may promote inflammation and paracrine secondary senescence in healthy tissues. DNMT2/TRDMT1 methyltransferase is implicated in the regulation of cellular lifespan and DNA damage response (DDR). In the present study, the responses to senescence inducing concentrations of doxorubicin and etoposide in different cancer cells with DNMT2/TRDMT1 gene knockout were evaluated, namely changes in the cell cycle, apoptosis, aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 63 publications
1
61
1
Order By: Relevance
“…We have previously shown that 2 h treatment with 100 µM HP promoted SIPS in normal human fibroblasts such as WI-38 and BJ cells that were accompanied by elevated levels of reactive oxygen species (ROS) [ 17 ]. In the present study, the same concentration of HP was used, but insulinoma cells were stimulated with HP for 24 h. 5-AzaC post-treatment (1 µM, 24 h) was applied as previously reported using a doxorubicin- and etoposide-induced senescence model using four genetically different cancer cell lines [ 11 ]. HP treatment reduced the cell number of both insulinoma cell lines, but the cytostatic effects of HP were more pronounced in β-TC-6 cells compared to NIT-1 cells ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that 2 h treatment with 100 µM HP promoted SIPS in normal human fibroblasts such as WI-38 and BJ cells that were accompanied by elevated levels of reactive oxygen species (ROS) [ 17 ]. In the present study, the same concentration of HP was used, but insulinoma cells were stimulated with HP for 24 h. 5-AzaC post-treatment (1 µM, 24 h) was applied as previously reported using a doxorubicin- and etoposide-induced senescence model using four genetically different cancer cell lines [ 11 ]. HP treatment reduced the cell number of both insulinoma cell lines, but the cytostatic effects of HP were more pronounced in β-TC-6 cells compared to NIT-1 cells ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…Cells were passaged by detaching with the trypsin-EDTA solution (Corning, Tewksbury, MA, USA, 25-053-CI). Both cell lines were seeded at the total number of 1 × 10 5 cells per well in a 6-well plate and cultured until approximately 70–80% confluency was reached (3 to 4 days) and then treated with 100 µM hydrogen peroxide (H 2 O 2 ) for 24 h (HP, Merck KGaA, Darmstadt, Germany) for the induction of oxidative stress, or with 1 µM 5-azacitidine for 24 h (5-azaC, Merck KGaA, Darmstadt, Germany) for the inhibition of methylation or cells were treated with 100 µM HP for 24 h and then the medium was discarded and cells were post-treated with 1 µM 5-azaC for 24 h. The concentrations of HP and 5-azaC were selected on the basis of our previously published protocols [ 11 , 17 ]. Except for the assay of senescence-associated β-galactosidase activity, all parameters were analyzed immediately after 5-azaC post-treatment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 33 TRDMT1 (tRNA aspartic acid methyltransferase 1), also known as DNMT2, promoting tRNA stability and protein synthesis, participates in cell cycle, apoptosis, autophagy and interleukin levels of many tumors. 34 , 35 However, there are few reports on the correlation between TRDMT1 and colon cancer. NSUN6 (NOP2/Sun RNA methyltransferase 6), is a member of the family of NSUN proteins, which is associated with tRNAs and acts as a tRNA methyltransferase.…”
Section: Discussionmentioning
confidence: 99%